PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN SUMENEP - Enza Resdiana (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
This self-assessment system is carried out in order to maximize the realization of local revenue which can affect the original revenue of Sumenep Regency. The purpose of this study was to find out how the self-assessment system collection system in increasing the revenue of the Regional Original Income Tax sector BPHTB. While the method used in this study is qualitative research, with data analysis techniques carried out through several stages ranging from data reduction, data presentation, to drawing conclusions. The results show that the BPHTB self-assessment system procedure in Sumenep Regency makes it easier for taxpayers to register and calculate the obligation to pay taxes and contribute to increasing local revenue, although there are obstacles in the reporting process where taxpayers are still not aware of reporting after paying BPHTB taxes. so that the process of recording and reporting is waiting for a checking account or transaction reporting from the bank. But all of that can be overcome with the skill and alertness of BPHTB tax officers in submitting reports so that the speed of presentation of data on the realization of regional original income can be presented in real time and accurately.